ISO 9000 quality systems certification and its impact on innovation performance - Terziovski, Mile; Guerrero-Cusumano, J. (Academy of Management, 2009)
This study examines the impact of ISO 9000 certification on innovation performance of a large number of Australian organizations. We conclude that ISO 9000 certification has a significant negative effect on performance dimensions related to product innovation and a significant and positive effect on performance dimensions related to process innovation.